Topography and Atomic Structure Investigations Of (100) Cleavage Surface of In4Se3 Layered Crystals - P.V. Galiy; T.M. Nenchuk; I.R. Yarovets (Журнал нано- та електронної фізики)
The atomic microstructure and crystallography of (100) surfaces of In4Se3 layered crystals obtained by cleavage in situ were studied by the methods of scanning tunneling and atomic force microscopies (STM, AFM) and low energy electron diffraction (LEED) for reflection. The obtained results indicate the existence of periodic corrugated structures on the cleavage surface. It is shown that (100) In4Se3 cleavage surface is structurally stable and doesn't undergo reconstruction in a wide temperature range of 77-295 K. The anisotropy of thermal expansion along the main crystallography directions in the (100) In4Se3 cleavage plane has been shown. The evaluation of the two-dimensional lattice constant in the cleavage (100) surface plane of orthorhombic In4Se3 layered crystal was done. The calculated values of the lattice constants in consequence of LEED study, such as b  11,475 Å and c  3,734 Å, coincide well with those obtained by the AFM and STM (b  13-14 Å and c  4 Å), and correlate, within the errors limits, with the corresponding values obtained by X-ray diffraction (b  12,308(1) Å and c  4,0810(5) Å). Besides, the obtained results of cleavage surface structure studies show the correctness of filtering application concerning topography images and indicate the adequacy of the model used for calculations of the cleavage (100) surfaces lattice constants of In4Se3 in accordance with the LEED results. The influence of the LEED experimental module structure on the results has been considered.